2021
DOI: 10.1021/acsomega.1c02971
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Advantages and Limitations of qPCR Duplexing in a Single Fluorescent Channel

Abstract: Real-time (quantitative) polymerase chain reaction (qPCR) has been widely applied in molecular diagnostics due to its immense sensitivity and specificity. qPCR multiplexing, based either on fluorescent probes or intercalating dyes, greatly expanded PCR capability due to the concurrent amplification of several deoxyribonucleic acid sequences. However, probe-based multiplexing requires multiple fluorescent channels, while intercalating dye-based multiplexing needs primers to be designed for amplicons having diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…112 Same goes to intercalating dye-based multiplex that require primers for each virus and having different melting temperatures. 113 Many laboratories apply singleplex real-time PCR for detection of RNA and DNA viruses. Diagnosis of cytomegalovirus (CMV) using qPCR in saliva sample had resulted with 100% sensitivity and 99.9% specificity as compared to rapid culture technique.…”
Section: Singleplex Qpcr and Multiplex Qpcrmentioning
confidence: 99%
See 2 more Smart Citations
“…112 Same goes to intercalating dye-based multiplex that require primers for each virus and having different melting temperatures. 113 Many laboratories apply singleplex real-time PCR for detection of RNA and DNA viruses. Diagnosis of cytomegalovirus (CMV) using qPCR in saliva sample had resulted with 100% sensitivity and 99.9% specificity as compared to rapid culture technique.…”
Section: Singleplex Qpcr and Multiplex Qpcrmentioning
confidence: 99%
“…96,120 Thus, it is critical during designing the probes and primers which must be specifically able to detect specific virus only, otherwise interactions between them will affect the efficiency of multiplex PCR assay. 113 A research made to assess performance of duplex RT-qPCR for detection of DENV and ZIKV showed a great analytical sensitivity as the limit of detection was similar when tested using singleplex assay. Plus, it also produced high specificity as no signals were measured from Flaviviridae family such as WNV, JEV, HCV, YFV and CHIKV.…”
Section: Singleplex Qpcr and Multiplex Qpcrmentioning
confidence: 99%
See 1 more Smart Citation
“…A compartmentalized sample forms a binary system of thousands or millions of subsamples, each containing a single copy or no copy of the target DNA. 5 This technique allows absolute quantification of selected target DNA sequences and, most importantly, performs multiplex PCR with minimal interaction between different targets, 6 distinguishing rare DNA targets from abundant ones. 7 The compartmentalization of the original sample is achieved either by filling predefined partitions forming a chip-based dPCR (cdPCR) 8 or by forming individual droplets as microreactors of a droplet-based dPCR (ddPCR).…”
Section: Introductionmentioning
confidence: 99%
“…The existing qPCR has achieved multiplex detection in a single fluorescent channel by collecting and analyzing the signals of the whole amplification procedure, e.g., amplification curves and melting curves, to classify different targets. [11][12][13][14][15] For dPCR, the multiplex detection in a single fluorescent channel can also apply a similar principle. 16 However, such a strategy needs to take images or measure fluorescence intensities after each amplification cycle to obtain a real-time signal, which requires sophisticated readout equipment and a complex analysis algorithm, limiting its widespread application and translation to commercial instruments.…”
Section: Introductionmentioning
confidence: 99%